Reducing prejudice through actual and imagined contact: A field experiment with Malawian shopkeepers and Chinese immigrants - Jun Gu; Annika Mueller; Ingrid Nielsen; Jason Shachat; Russell Smyth (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2015)
We examine the ability of intergroup contact to ameliorate the effect of in-group bias on economic outcomes. Specifically, we employ randomized experiments to test whether actual and imagined contact is effective in reducing prejudice between indigenous Malawian shopkeepers (in-group), and their Chinese immigrant counterparts (out-group), and test the stability of these changes over time. We find differing results with actual contact. Local Malawians attitude towards Chinese migrants did not improve, but their willingness to spend time did. In contrast, actual contact spurred improvement in the Chinese migrants attitude toward local Malawians, but did not increase their willingness to spend time with them. These effects persisted over a time period of at least ten days. Imagined contact had no impact on Malawians attitude or behavioral intention with respect to Chinese migrants
Keywords: C93; J15; O19; 330; Chinese migrants in Africa; actual contact; imagined contact; prejudice; field experiment